Phase I study of loracarbef - Shiba, Kohya; Kobayashi, Satoshi (CHEMOTHERAPY, 1993)
The safety and pharmacokinetics of loracarbef (LCBF), a new carbacephem derivative, were examined in 34 healthy male volunteers in a single-or multiple-dose study.In the single-dose study, subjects were administered an oral dose of 100, 200 or 400 mg.In the multiple-dose study, subjects were divided into two groups for LCBF treatment and for placebo treatment.The subjects from the active and placebo groups were administered 200 mg or 400 mg of LCBF or placebo t.i.d. for 7 days. 1.No changes attributable to LCBF were observed in clinical signs and symptoms, physical tests, laboratory tests, antihemorrhage-coagulation tests or renal function tests in any study. 2.The plasma concentration of LCBF peaked at about 1h after single dosing and decreased with a half life of 0.94-1.18 h.After doses of 100, 200 and 400 mg, AUC were 6.88, 14.6 and 30.7μg·h/ml and urinary recovery was 91.5, 93.5 and 91.5% of the dose, respectively. 3.The decrease in peak plasma concentration and prolongations of Tmax and MRT in the fed state were significantly different compared with the fasting state.No difference in urinary recovery rate was found in either state. 4.No accumulation of LCBF in plasma was observed after multiple administrations of LCBF (200 mg or 400 mg t.i.d.) for 7 days 5.Active metabolites of LCBF were not detected in plasma or urine.